2020
DOI: 10.1063/5.0016510
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the ultraviolet photoluminescence of ZnO films: Coatings, annealing, and environmental exposure studies

Abstract: To realize the many potential applications of ZnO films, it is vital to produce films with high optical quality that exhibit strong UV luminescence. By combining annealing at an optimal temperature followed by the deposition of a coating, one can achieve a significant enhancement of photoluminescence (PL). The effectiveness of the coating over time is a crucial point to be considered. Three types of coating materials were investigated: MgO, SiO2, and Al2O3. Due to its strong bond energy, MgO was found to be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…On the other side, the observed enhancement of luminescence intensity of both components under Alq 3 deposition can be caused by mutual in uence of each other. It has been found that passivation of ZnO lms by coatings with metal oxides [45] and doping with hydrogen [46] result in the strong UV ZnO luminescence enhancement. Alq 3 contains oxygen atoms and a lot of hydrogen atoms to promote this process.…”
Section: Resultsmentioning
confidence: 99%
“…On the other side, the observed enhancement of luminescence intensity of both components under Alq 3 deposition can be caused by mutual in uence of each other. It has been found that passivation of ZnO lms by coatings with metal oxides [45] and doping with hydrogen [46] result in the strong UV ZnO luminescence enhancement. Alq 3 contains oxygen atoms and a lot of hydrogen atoms to promote this process.…”
Section: Resultsmentioning
confidence: 99%
“…As such substitution is possible for luminescent applications, the search for RE-free luminescent materials becomes a significant task. For a long time, ZnO-based materials have attracted considerable attention for possible applications in optoelectronic devices, particularly in the ultraviolet (UV) light emitters [9][10][11][12]. Visible-light-emitting materials with various spectral properties could also be obtained on the basis of ZnO because both blue luminescence and green luminescence have already been reported in the modified ZnO structures [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Therefore, strategies to enhance the NBE consist of supressing defect formation during synthesis or post-growth. 16,17 Several, methods have been investigated to that end, which include surface state modification of ZnO by TiO 2 and Al 2 O 3 capping layers; hydrogenation [18][19][20] ; annealing under N 2 and O 2 [21][22][23] ; controlling defects during synthesis itself 24,25 ; and conjoining them with metal nanoparticles displaying surface plasmon resonance. 26,27 Organic and inorganic materials have witnessed enhancements in physical, chemical and structural properties when combined with CNT.…”
Section: Introductionmentioning
confidence: 99%